EFFECTIVENESS OF RESINS/EXUDATES OF TREES IN CORROSION PREVENTION OF REINFORCEMENT IN REINFORCED CONCRETE STRUCTURES (Nigerian Journal of Technology, 2017)
Corrosion of steel reinforcement is one of the important factors that are responsible for the short service life of reinforced concrete members, in marine structures like bridges, piers and jetties. This study, investigated the effectiveness of resin/exudates in corrosion prevention of reinforcement in reinforced concrete cubes. The reinforced concrete cubes of dimension (150mm x 150mm x 150mm) were coated with dacryodes edulis resin paste of various thicknesses: 150um, 250um, and 300um. The reinforced concrete cubes were exposed to a corrosive environment for 60days after 28 days of curing. in order to stimulate accelerated corrosion of the reinforcing steel. Another test was carried out with steel reinforcement cubes, whose steel reinforcement were not coated with dacryodes edulis resin but also exposed to the same corrosive environment. for the same 60 days after 28 days curing. The control test was carried out with a set of concrete cubes that were not coated with dacryodes edulis but were not exposed to a corrosive environment. The reinforced concrete cubes were subjected to tensile and pull out bond strength in order to access the effectiveness of the resin on the corrosion prevention, by enhancing the tensile and pull out bond strength of the reinforcement in the experimental cubes. Results obtained indicated that the failure bond strength, pull out bond strength and maximum slip of the resin coated reinforced cubes were higher by (19%), (84%) and (112%). respectively than those obtained from the controlled tests. Similar results were obtained for the maximum slip (the resin coated and non-corroded steel members) had higher values of maximum slip compared to the cubes that had corroded steel reinforcements. For the corroded beam members, the failure bond strength, pull out bond strength and maximum slip of the resin coated reinforcements were lower by (22%), (32%) and (32%). respectively than those obtained from the controlled tests. The resin (mdacryodes edulis) inhibit corrosion of the reinforcement, hence enhanced strength to the reinforcement.http://dx.doi.org/10.4314/njt.v37i1.11